PELATIHAN KETRAMPILAN PENGELASAN UNTUK KELUARGA PRA-SEJAHTERAH DI DAERAH LATIHAN TARUNA AKMIL - Aryananta Lufti; Budi Harjanto; Sukahar (JURNAL NAGARA BHAKTI, 2023)
The number of pre-prosperous families in Kalisari subdistrict Tempuran, Magelang regency is still many, there is a strong fact that unemployment is the main factor.Akmil, especially the Defense Mechanical Engineering Study Program, wants to take part in overcoming these problems by providing special skills training to the people of the village,so that they can provide skills that allow them to obtain jobs that are in accordance with the skills obtained from the training.Laboratory TeknikMesin Akmil defense has a fairly complete welding equipment, supported by experienced technicians and instructors can be used to support training programs especially in the field of basic level welding. The basic level welding training Program has been successfully carried out in 2017, 2018,2019, and 2020 with a very positive response from the participants who directly benefited from this training. The skill level obtained in basic welding training includes, arc ignition, 1G and 1F horizontal position welding, security, equipment/clothing and eye protection. The training in 2020 was attended by 11 participants. So that in total from the first batch of 2017 to 2020 there were 41 trainees who had participated.